QUANTITATIVE METHODOLOGY FOR ANALYZING THE WATER-ENERGY-FOOD NEXUS IN RIVER BASINS UNDER HISTORICAL AND FUTURE SCENARIOS - DA SILVA, Tamires Lima [UNESP]; Román, Rodrigo Máximo Sánchez [UNESP]; Sarjoughian, Hessam S.; Fard, Mostafa D. (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2024)
The integrated use of water, energy, and food resources is essential for the sustainable management of river basins. This study developed a quantitative methodology to model the water‒energy‒food (WEF) nexus in river basins, considering both historical conditions and future projections. The proposed methodology uses models created in the “Water Evaluation and Planning” System (WEAP) and “Low Emissions Analysis Platform” (LEAP) programs, which were coupled for data exchange through the WEAP-KIB-LEAP framework. To exemplify the use of the methodology, an application was carried out in the Piracicaba, Capivarí and Jundiaí (PCJ) river basins. The results showed that the tool allows the WEF nexus to be simulated, offering valuable support for the sustainable planning of the resources present in the PCJ basins, and can contribute to achieving the Sustainable Development Goals (SDGs). It is recommended that the framework be applied in different regional contexts to expand its validation and applicability.
METODOLOGIA QUANTITATIVA PARA ANÁLISE DO NEXO ÁGUA-ENERGIA-ALIMENTO EM BACIAS HIDROGRÁFICAS SOB CENÁRIOS HISTÓRICOS E FUTUROS
Keywords: LEAP; WEAP; WEAP-KIB-LEAP framework; WEF nexus